Shocked POststarburst Galaxy Survey. IV. Outflows in Shocked Poststarburst Galaxies Are Not Responsible for Quenching - Antoniu Fodor; Taylor Tomko; Mary Braun; Anne M. Medling; Thomas M. Johnson; Alexander Thompson; Victor D. Johnston; Matthew Newhouse; Yuanze Luo; K. Decker French; Justin A. Otter; Akshat Tripathi; et al. (The Astrophysical Journal)
Shocked POstarburst Galaxies (SPOGs) exhibit both emission lines suggestive of shock-heated gas and poststarburst-like stellar absorption, resulting in a unique subset for galaxy evolution studies. We have observed 77 galaxies that fulfilled the SPOG criteria selection using the DeVeny Spectrograph on the Lowell Discovery Telescope. Our long-slit minor axis spectra detect H α and [O III ] in some SPOGs out to 6 kpc above the galactic plane. We find extraplanar ionized gas in 31 targets of our sample overall. Using their internal and external kinematics, we argue that 22 galaxies host outflows with ionized gas masses ranging from 10 ^2 M _⊙ to 10 ^5 M _⊙ . The rest are likely extended diffuse ionized gas. A positive correlation exists between active galactic nuclei (AGN) luminosity and the extraplanar gas extent, velocity dispersion, and mass—suggesting that the AGN may indeed drive the outflows detected in AGN hosts. The low masses of the extraplanar gas suggest that these outflows are not depleting each galaxy’s gas reserves. The outflows, therefore, are not likely a significant quenching mechanism in these SPOGs.